The efficacy of hiring credits in distressed areas - Jorge Pérez Pérez; Michael Suher (Banco de México, 2020)
We analyze the efficacy of hiring tax credits, particularly in distressed labor markets. These types of programs have proven hard to assess as their introduction at the state level tends to be endogenous to local conditions and future prospects. We conduct an empirical study of a hiring tax credit program implemented in North Carolina in the mid 1990s, which has a quasi-experimental design. Specifically, the 100 counties in the state are ranked each year by a formula trying to capture their economic distress level. The generosity of the tax credits jumps discontinuously at various ranking thresholds allowing for the use of regression discontinuity methods. Our estimates show fairly sizable and robust impacts on unemployment - a 9,000 credit leads to a nearly 0.5 percentage points reduction in the unemployment rate in the counties where the credit was made available. The attendant increase in employment levels appears to be around 3%.
Keywords: J2; R14; 330; Hiring tax credits; employment; local labor markets